How is organic fertilizer produced and applied to chili and eggplant plants? - Eny Dyah Yuniwati; Rani Darmayanti; Syed Muhammad Yousaf Farooq (AMCA Journal of Community Development, 2023)
Organic fertilizers increase plant growth and yield by improving soil properties. Judging from the physical properties of the soil, organic fertilizer can increase the soil's ability to hold water, thereby increasing plant access to water. This research aims to discover how to make organic fertilizer from rice husks and apply it to vegetable plants. Counseling, training, implementation, and program evaluation are the methods. The research results showed that fermented rice husk organic fertilizer was applied directly to various vegetable plants previously planted in the nursery. Several vegetable plants, including chili and eggplant, are sown in polybags. Plant growth in polybags using organic planting media is quite good because the soil properties improve from the organic fertilizer provided. Improving soil properties means improving physical, chemical, and biological properties. Exciting things were discovered from this research. The facts and how alert farmers were when the main ingredients for making fertilizer were very scarce to obtain will be discussed